Response of different fertigation levels and cultivars of strawberry (Fragaria × ananassa) on yield and economic benefit - Neelam Dev; Yogendra Singh; Vikash Prasad Mishra; Deepak Kher; Yashpal Singh Bisht; Yogendra Kumar Sharma; Divya Slathia (Current Horticulture, 2024)
A field study was conducted to evaluate the “response of different fertigation levels and cultivars of strawberry (Fragaria × ananassa Duch.) on yield and economic benefit” at the Department of Horticulture, Dr. K.S.G.A. College of Agriculture, Eternal University, Baru Sahib (HP) during 2021-2022. The experiment was set up using a Factorial Randomized Complete Block Design with 12 treatment combinations, which included four levels of fertigation (0%, 50%, 75%, and 100%) and three cultivars (Camarosa, Chandler, and Winter Dawn) and replicated thrice. The maximum value of fruit setting (99.21 %), number of flowers/plant (20.36), yield/plant (425.27 g) and yield/plot (5.10 kg) were noted in fertigation level F3 (100% recommended dose of NPK). The highest fruit setting (96.58 %), number of flowers/plant (19.14), yield/plant (381.31 g), yield/plot (4.57 kg) were recorded under “Chandler” cultivar whereas, maximum fruit setting (98.91 %), yield/plant (442.18 g) and yield/plot (5.30 kg) were obtained with treatment combination T12 (Camarosa+100% RDF dose of NPK through drip) as compared to other treatments. The maximum Cost: benefit ratio (3.31) was observed in treatment combination T12 (camarosa with 100% recommended dose of NPK through drip).